2002
DOI: 10.1046/j.1365-2249.2002.01752.x
|View full text |Cite
|
Sign up to set email alerts
|

CD40 on salivary gland epithelial cells: high constitutive expression by cultured cells from Sjögren’s syndrome patients indicating their intrinsic activation

Abstract: SUMMARYCD40 has been identified in an expanding list of haematopoietic and non-haematopoietic cells and has received an increased interest based on its role in a variety of cell-mediated responses and its potential to participate in the pathogenesis of chronic inflammatory disorders. Sjögren's syndrome (SS) is an autoimmune exocrinopathy, which is characterized by chronic lymphocytic infiltration of exocrine glands and aberrant activation of epithelial tissues. We studied the expression of CD40 protein in cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
78
0
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 35 publications
7
78
0
7
Order By: Relevance
“…CD40 is a 45-50 kDa phosphorylated type I integral membrane glycoprotein that belongs to the tumor necrosis factor receptor superfamily, which is expressed on various hematopoietic and non-hematopoietic cells (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). CD40 is involved in several biological functions, such as cell-mediated immunity and cell growth regulation.…”
Section: Introductionmentioning
confidence: 99%
“…CD40 is a 45-50 kDa phosphorylated type I integral membrane glycoprotein that belongs to the tumor necrosis factor receptor superfamily, which is expressed on various hematopoietic and non-hematopoietic cells (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). CD40 is involved in several biological functions, such as cell-mediated immunity and cell growth regulation.…”
Section: Introductionmentioning
confidence: 99%
“…As stated earlier, in an in vitromodel using HSG cells that α-fodrin, caspase-3, poly(ADP-ribose) polymerase protease (PARP), SS-A, and SS-B were all cleaved in response to stimulation by TNF-α, a known inducer of apoptosis [21].Therefore, it is possible that TNF, which is increased systemically in SS, contributes in vivo to apoptosis and destruction of salivary gland tissue. TNF-α and other cytokines such as IFN-γ are known to be increased in vivoin the parenchyma of salivary and lacrimal glands of patients with SS [22][23][24][25][26].The cellular source of TNF in the salivary glands is unknown, however, although it is presumably released by infiltrating CD4 lymphocytes.…”
Section: Discussionmentioning
confidence: 86%
“…TNF-α and other cytokines such as IFN-γ are known to be increased in vivoin the parenchyma of salivary and lacrimal glands of patients with SS [22][23][24][25][26].The cellular source of TNF in the salivary glands is unknown, however, although it is presumably released by infiltrating CD4 lymphocytes. Interestingly, all proteins except PARP are cleaved in vitroand transported to the ductal or acinar cell membrane; PARP, however, is cleaved but remains in the intracellular space [21].Perhaps this intracellular location of PARP where it appears protected from antigen processing by the immune system, is one factor contributing to why PARP is infrequently associated with autoantibody production in SS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epithelial cells are thought to participate in and modulate the inflammatory process in SS, as supported by previous immunohistochemical studies of the salivary gland tissue of SS patients that demonstrated an increased expression of various immunoactive molecules in the ductal and acinar salivary gland epithelial cells (SGEC) [4][5][6][7][8][9]. Additionally, several studies of cultured SGEC from SS patients found that various molecules associated with innate and acquired immune responses were expressed [10][11][12][13][14]. These results strongly suggest the implication of epithelial cells in the induction and promotion of chronic inflammation and that they have an important role to play in the pathogenesis of SS.…”
Section: Introductionmentioning
confidence: 86%